Enhancing Phonological Awareness in Early Literacy through Digital Tools: A Qualitative Literature Review on Effectiveness and Engagement - Naeem, Farhan Muhammad; Khan, Muhammad Kamal (Pakistan Languages and Humanities Review, 2024)
Phonological awareness is an essential part of early literacy — it lays the groundwork for strong reading and writing skills. Many digital tools have been developed in the light of new technologies, which play an important role nowadays for teaching this skill to children. The purpose of this study is to provide a systematic review and qualitative analysis in the literature relating digital intervention content targeting phonological awareness. The evaluation is based on how the tools actually improved phonological capabilities, balanced engagement/enthusiasm as well as the overall educational value The results indicate that digital tools with interactive components, instant feedback and adaptive learning pathways have a positive influence on these skills. Furthermore, they reach all types of learners (reading, visual, auditory) — literacy can be learned and experienced in a way that is convenient and friendly across the board. This is crucial in the current context where digital technology has gained center stage as a facilitator of all forms of language learning, therefore this study will provide useful insights to educators who wish to use such tools in their teaching. In addition, it points out that future studies need to be done to enhance the application of digital tools in relation to early literacy development.